Current System of National Bibliographic Resources of the Sakha Republic (Yakutia) - Sargylana V. Maksimova; Саргылана Васильевна Максимова (Bibliotekovedenie [Library and Information Science (Russia)], 2018)
The current state of the national bibliography in the Republic of Sakha (Yakutia), worked out in 2000—2017, is analysed. The main types of national bibliographic indexes — current and retrospective — are considered. The author describes the existing system of national bibliographic resources, its methodological, organizational and technological development. It is noted that currently there are determined the bibliographing centers of the Republic — the main participants in the creation of national bibliographic indexes. The author reveals the specific features of the development of the modern national bibliography of Yakutia in the main areas: state (current national) bibliographic control of the legal deposit copy of documents of the Republic of Sakha (Yakutia); development of the retrospective national bibliographic repertoires. The emphasis is made on the activities of the National Library of the Republic of Sakha (Yakutia), which processes all national and regional documents published in the Republic and beyond its borders. The current organizational structure is analysed, considering seventeen-year experience of formation of the system of national bibliography, creation of the National Bibliographing Agency and resumption of issue of State Bibliography Indexes. There are described the materials of the long-term plan for creation of system of retrospective national bibliography of the Republic of Sakha (Yakutia) for the period up to 2020, which regulates the development and defines the main organizational activities for its formation, as well as contains information about specific projects. There are characterized the key National Retrospective Indexes: “Bibliography of the Bibliography of Yakutia (1838—2000)”, “Yakut Book (1917—1957)”, “Union Catalogue of the Yakut Books (1812—1917)”, “Books in the Languages of the Indigenous Minorities of the Sakha Republic (Yakutia)”, “Book Culture of the Evens”, “Book Culture of the Evenks”. The results of development and the features of the modern system of national ...